Deep Parotid Lobe Abscess Presenting with Dysphagia and Trismus - Madison Grinnell; Andrew Logeman; Timothy Knudsen; Zafar Sayed (Case Reports in Otolaryngology)
An abscess of the deep parotid lobe is an uncommon complication of acute parotitis. Characterized by warm erythematous facial skin and ipsilateral cheek swelling, parotid abscesses have often been associated with decreased saliva production and immunodeficiency. We offer a case of a large deep parotid lobe abscess presenting similarly to a peritonsillar mass, causing significant odynophagia and difficulty swallowing. Computed tomography scan revealed an infected deep parotid lobe sialocele which was surgically drained transorally and treated expectantly with antibiotics.